Importance of adequate diagnostic workup for correct diagnosis of advanced systemic mastocytosis - Schwaab, Juliana; Cabral do O Hartmann, Nicole; Naumann, Nicole; Jawhar, Mohamad; Weiß, Christel; Metzgeroth, Georgia; Schmid, Alicia; Lübke, Johannes; Reiter, Lukas; Fabarius, Alice; Cross, Nicholas C. P.; Sotlar, Karl; et al. (The journal of allergy and clinical immunology. In practice, 2020)
Background - Little is known about the epidemiology of advanced systemic mastocytosis (advSM). - Objectives - To investigate epidemiologic features and diagnostic pitfalls of advSM in Germany. - Methods - Therefore, 140 patients from a single German reference center of the European Competence Network on Mastocytosis between 2003 and 2018 were analyzed. - Results - The patients' median age was 68 years (range, 26-86 years), and male versus female ratio was 2:1. An elevated serum tryptase, a KIT D816 mutation, and additional somatic mutations, for example, in SRSF2, ASXL1, or RUNX1, were identified in 95%, 91%, and 74% of patients, respectively. Median overall survival was 3.5 years (range, 0.03-14.3 years; male vs female 2.6 vs 4.2 years; P = .02). Two categories of misdiagnoses were identified in 51 of 140 (36%) patients: First, systemic mastocytosis (SM) was overlooked in 28 of 140 (20%) patients primarily diagnosed with various subtypes of myeloid neoplasms. Second, 23 of 140 (16%) patients were diagnosed with supposed progression from indolent SM to advSM; however, combination of an elevated KIT D816V variant allele frequency in peripheral blood (n = 22), monocytosis (n = 9), eosinophilia (n = 6), and/or mutations in SRSF2, ASXL1, or RUNX1 (n = 10) suggest that distinct signs of potential advSM were overlooked in virtually all patients. Based on locally diagnosed patients in an area of 2.5 million inhabitants, but obviously without considering more, yet unrecognized cases, the incidence and prevalence of advSM is at least 0.8 and 5.2, respectively, per 1 million inhabitants. - Conclusions - Adequate analyses of tryptase levels, bone marrow morphology, and genetics in patients with myeloid neoplasms or SM would help to prevent the significant underdiagnosis of advSM.
Online verfügbar: 15. Mai 2020
Gesehen am 30.06.2025